Women healers : gender, authority, and medicine in early Philadelphia - Brandt, Susan Hanket (Early American studies., 2022)
"Women Healers recovers Euro-American, Native American, and Black women's authoritative practices in the Philadelphia area during the long eighteenth century. Women developed healthcare authority and produced new scientific knowledge by participating in medical information networks, science education, health reform, and a consumer healthcare marketplace. Professional women physicians, pharmacists, and nurses built on this foundation"--